Asynchronously finite-time H∞ control for morphing aircraft. (December 2018) - Cheng, Haoyu; Fu, Wenxing; Dong, Chaoyang; Wang, Qing; Hou, Yanze
This paper investigates the problem of asynchronously finite-time H ∞ control for morphing aircraft with controller uncertainties. Based on the switched linear parameter-varying model of morphing aircraft, the inherent packet dropouts of system are taken into consideration, which will lead to asynchronous switching. The asynchronous switching means that the switching of controllers will lag behind the switching of corresponding subsystem. Moreover, in order to overcome the undesirable influence of controller uncertainties and guarantee that the corresponding closed-loop system is finite-time bounded with a specified H ∞ performance index, the non-fragile finite-time H ∞ controller is developed via asynchronously switched control. For the purpose of less conservative controller design, the finite-time robust stability analysis of the system is verified by combining mode-dependent average dwell time method and multiple Lyapunov functional method. The sufficient existing conditions and solutions of the controllers are found by solving a series of linear matrix inequalities. Finally, the method proposed in this paper is demonstrated by an illustrative numerical example.